Variability in a collection of fenugreek (Trigonella foenum-graecum L.) germplasm - YADAV, R K (Journal of Spices and Aromatic Crops, 1999)
Fenugreek (TrigoneUa foenum-graecum L.) is an important spice grown in many parts of Madhya Pradesh, India. Surveys were conducted for collection of fenugreek germplasm from Jabalpur of Madhya Pradesh during 1996-97. The collections were sown at Regional Agricultural Research Station, Raigarh, Madhya Pradesh, for evaluation and some of their morphological attributes are presented in Table 1.